مساهمة في دراسة سلوك الجوائز الفولاذية الحاوية على فتحات في الجسد - شيخ علي غسان; عيسى نعمان; دو علي (Latakia University Journal -Engineering Sciences Series, 2019)
تتوضع الفتحات في أجساد الجوائز الفولاذية لتسمح بتمرير التجهيزات الفنية للمنشآت الصناعية والمباني، مما يتطلب من المهندس العامل في مجال تصميم المنشآت الفولاذية، معرفة السلوك الإنشائي لهذه الجوائز ومدى تأثير هذه الفتحات في الحد الأقصى للمقاومة وحد الاستثمار، وإيضاح آلية تدعيم مناطق الفتحات عند الضرورة بشكل يلائم المتطلبات الفنية ويؤدي في الوقت نفسه إلى زيادة طاقة تحملها لتعويض النقص الحاصل من جراء وجود الفتحات. إن الهدف الأساسي من البحث هو دراسة سلوك هذه الجوائز، ونظرا" لشمولية البحث واتساعه فقد اقتصر على متحولات محددة كشكل الفتحة وأبعادها مع التركيز على الفتحات الدائرية والمربعة بغية الوصول إلى الحل الأمثل لتوضع هذه الفتحات واقتراح آلية التدعيم المناسبة لها. وقد توصل الباحث إلى أن إضافة تدعيم يعادل نسبة (45%) من مساحة الجناح تساهم إلى حد كبير بزيادة طاقة التحمل لهذه الجوائز لتقترب من طاقة تحمل الجوائز الأصلية(غير الحاوية على فتحات) كما أن تخفيض الفتحات الدائرية لطاقة التحمل هو أقل بكثير من الفتحات المربعة. The openings in the webs of steel beams exist in order to allow the passage of technical equipment to industrial structures and buildings. The engineer working in the field of designing steel structures is required to know the structural behavior of these beams and the effect of these openings on the maximum limit and the limit of investment, and illustrate the mechanism of reinforcing the openings when necessary in such a way that meets the technical requirements increase the capacity of their endurance to compensate for the loss resulting from the presence of the openings. Therefore, the basic goal of this paper is studying the behavior of these beams. Due to the paper being wide-ranging, we have confined it to defining variables such as the opening form and its dimensions along with concentration on the circular and square openings for reaching the optimal solution to the setting of these openings and suggesting the suitable reinforcement mechanism. The researcher has concluded that adding reinforcement at the rate of 45 % of the flange area contributes to a large extent to the increase of the endurance capacity for these beams in comparison with the free from openings beams, and that reducing the endurance capacity as a result of the circular openings is far less than the Square openings.